Drug delivery platform for targeting osteosarcoma - Güler, Ülkü. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Drug delivery systems remain a challenge in the management of cancer and wide variety of diseases. Polymers containing different functional groups are widely used in the delivery of drugs. The molecular weight of the polymer is very crucial to achieve the targeted drug delivery and enhanced permeability and retention (EPR) effect. In this thesis, we utilized reversible addition-fragmentation chain transfer (RAFT) polymerization method to prepare high-molecular weight and water-soluble polymers which bear bisphosphonate groups along with anti-cancer agents on their side chains. Bisphosphonic acids have high affinity to the hydroxyapatite in the bone tissue, rendering them suitable ligands for bone targeting. The final constructs carrying chemotherapy agent linked to the polymer by activated carbonate group and targeting moiety will be evaluated in vitro for drug release and in terms of targeting efficiency.
Keywords: Drug delivery systems.; Osteosarcoma.